Research on Seawater Laser Communication Channel Based on Visible Light - Wang, Fei (2021 IEEE Asia-Pacific Conference on Image Processing, Electronics and Computers (IPEC), 2021)
In this paper, the optical characteristics of seawater laser communication channel in offshore waters are analyzed, and the transmission process of the seawater channel by Monte Carlo method, we get the statistical chart of the received power under different transmission distances. The results show that the fitting error of circular arc algorithm is less than that of Gaussian function. Based on the circular fitting algorithm, the underwater wireless optical communication channel model is established. According to the transmission model, the relationship among laser transmission distance, arbitrary receiving position and receiving power can be quickly obtained under certain sea water quality parameters, which provides valuable reference for the design of underwater wireless optical communication system.